PELATIHAN AKUNTANSI UNTUK PENYELENGGARAAN PEMBUKUAN SEDERHANA BAGI KUBE JAYA ABADI DESA PENGUDANG - Sarazwati, Raja Yulianita; Mu’azamsyah, Muhammad; Ellmanda, Devis; Kamelda, Kamelda; Carolina, Meidi; Nisyamuddin, Nisyamuddin; Juwita, Rahma Dini; Waskitho, Thessalonica Mutiara (P3M STIE Pembangunan Tanjungpinang, 2025)
Simple bookkeeping is a documentation process carried out by employers in a structured manner by collecting data and information related to the company's financial reports. Usually, this simple bookkeeping consists of all financial reports in a company. Financial documentation that is recorded is usually related to assets, expenses, capital, income , budget, prices with output results in the form of presentation of financial reports. The purpose of bookkeeping activities in a business is to reduce or minimize the risk of losing products, assets, and even money belonging to the company. The problem we encountered in Pengudang Village, more precisely at KUBE Jaya Abadi is these business actors do not yet know the importance of a bookkeeping. As a result, they do not know how much their income and expenses are while their business is running. For this reason, we held an